Competency-Based Medical Education (CBME)- An Incremental Boon For Undergraduate Medical Students of India - Alinawaz Khan; Sanjeev I Kolagi; Anita Herur (International Journal of Medical Students)
BACKGROUND: Competency based education has been defined as a result-based program to design, implement, assess and evaluate medical education using an organizing framework of competencies. According to the vision document put forth by MCI, thi undergraduate medical education program was designed with a goal to create an Indian Medical Graduate (IMG) possessing requisite knowledge, skills, attitudes, values, and responsiveness, so that he or she may function appropriately and effectively as a "physician of first contact" of the community while being globally relevant too. Albeit the CBME curriculum has been introduced in country since 5years, but such evaluation of the curriculum has not been carried out so extensively so far. Hence, this study fulfills the need of the hour and may suggest to rectify the education system accordingly in the nation as well as being a role model for other nations.